On Get Out and the Problem of Racialized Aliveness. Issue 3 (3rd July 2019) - Barnett, Rebecca
ABSTRACT: In this short article, I explore Jordan Peele's 2017 film Get Out as a compelling illustration of racialization as an attack on human "aliveness." I argue that Peele's film, a new kind of zombie narrative, urges psychosocial transformation not only through the radically inventive acts of its creatively resurrected protagonist, Chris, but also through its own subversive collaboration with the spectator.